"But what would they think of us?" Propaganda and the Manipulation of the Anglo-Soviet Occupation of Iran, 1941‒46. Issue 5 (2nd September 2016) - Abdul-Razak, Rowena
Abstract : The 1941 Anglo-Soviet occupation of Iran is a topic that continues to interest historians. Work on this period has mainly focused on the reasons behind the occupation and its impact on the political situation in the country. This article looks at the psyche of the occupying forces by studying their propaganda tactics during this period. It was through propaganda that both were able to manipulate local players to either further their own interests or damage the reputation of the other. Such tactics were reflective of the dynamic nature of British‒Soviet relations and had a direct consequence on the politics of Iran. A key aspect of this was the British machine's promotion of the Tudeh Party's legacy as a tool of the Soviets. The propaganda patterns reveal the reactive nature of the occupying force's policy in Iran, and reflected their changing interests.